Population structure of Bathymodiolus manusensis, a deep-sea hydrothermal vent-dependent mussel from Manus Basin, Papua New Guinea - Andrew D. Thaler; William Saleu; Jens Carlsson; Thomas F. Schultz; Cindy L. Van Dover (PeerJ, 2017)
Deep-sea hydrothermal vents in the western Pacific are increasingly being assessed for their potential mineral wealth. To anticipate the potential impacts on biodiversity and connectivity among populations at these vents, environmental baselines need to be established. Bathymodiolus manusensis is a deep-sea mussel found in close association with hydrothermal vents in Manus Basin, Papua New Guinea. Using multiple genetic markers (cytochrome C-oxidase subunit-1 sequencing and eight microsatellite markers), we examined population structure at two sites in Manus Basin separated by 40 km and near a potential mining prospect, where the species has not been observed. No population structure was detected in mussels sampled from these two sites. We also compared a subset of samples with B. manusensis from previous studies to infer broader population trends. The genetic diversity observed can be used as a baseline against which changes in genetic diversity within the population may be assessed following the proposed mining event.